Study on the Binary Resistive Modulation technique of the PLCC Technology in the Streetlamp Monitoring System - Tao, Jiang; Md Johar, Md Gapar; Tham, Jacquline (International Journal of Computer Science and Information Technology, 2024)
As a low-cost, open, and extensively covered communication technology, power line carrier communication (PLCC) technology has been applied to the streetlamp monitoring system to improve management quality. However, existing PLCC technologies face two problems: i. Significant signal attenuation on the power line, which limits transmission distance; ii. Inability to transmit signals across transformers due to the signal-blocking effect of transformers. To solve the problems, this paper introduces the resistive modulation technique into PLCC technology. Experiments show that the designed communication system has two advantages: i. It can transmit signals over long distances, as signal attenuation on the power line is suppressed; ii. It can transmit signals across the transformer as resistive signals are amplified when they are transmitted across the transformer.